Clinical Correlations of Transcriptional Profile in Patients Infected With Avian Influenza H7N9 Virus. (28th May 2018) - Guan, Wenda; Yang, Zifeng; Wu, Nicholas C; Lee, Horace H Y; Li, Yimin; Jiang, Wenxin; Shen, Lihan; Wu, Douglas C; Chen, Rongchang; Zhong, Nanshan; Wilson, Ian A; Peiris, Malik; et al.
Abstract : This study correlated serial blood transcriptomic profiles of patients with avian influenza A (H7N9) virus infection with clinical data of patients. Biologically significant transcriptomic profiles associated with blood oxygenation and viral load in the lower respiratory tract were defined. Abstract: Background: Avian influenza A (H7N9) viruses emerged in China in 2013 and caused zoonotic disease associated with a case-fatality ratio of over 30%. Transcriptional profiles in peripheral blood reflect host responses and can help to elucidate disease pathogenesis. Methods: We correlated serial blood transcriptomic profiles of patients with avian influenza A (H7N9) virus infection and determined the biological significances from the analysis. Results: We found that specific gene expression profiles in the blood were strongly correlated with the Pao 2 /Fio 2 ratio and viral load in the lower respiratory tract. Cell cycle and leukocyte-related immunity were activated at the acute stage of the infection while T-cell functions and various metabolic processes were associated with the recovery phase of the illness. A transition from systemic innate to adaptive immunity was found. Conclusions: We developed a novel approach for transcriptomic analysis to identify key host responses that were strongly correlated with specific clinical and virologic parameters in patients with H7N9 infection.